THE DEFINITION OF EMOTIONAL STATE IN REAL TIME - Vsevolod Novikov; Chernozub V.P. (Biomedicinskaâ Inženeriâ i Èlektronika, 2017)
In this work it was determined which emotion is essential for a potentially dangerous person in the service of Emotion the API, with the help of a program LiveCameraSample